Analisis Pendidikan Demokrasi terhadap Kesadaran Politik Generasi Muda di Era Modern - Della Nurahma; Alya Nur Hasanah; Zaenul Slam (Pancasila and Civics Education Journal (PCEJ), 2026)
Abstract: Democratic education plays a strategic role in fostering the political awareness of young people amid rapid technological advancements and the increasingly complex transformation of the digital public sphere. This study aims to analyze the influence of democratic education on the political awareness of young people in the modern era. The research employs a qualitative approach using a literature review method based on relevant journal articles, books, and scientific documents. The analysis was conducted through the identification, selection, and synthesis of various research findings related to democratic education, political awareness, and digital literacy. The findings indicate that democratic education contributes to enhancing young people's understanding of their rights and responsibilities as citizens, strengthening political participation, and developing critical thinking skills toward various social, political, and public policy issues. Furthermore, digital media serves as a platform that expands access to political information and opportunities for civic participation. However, low levels of digital literacy may increase the risk of misinformation and disinformation. Therefore, the integration of democratic education and digital literacy is essential to foster a generation of young citizens who are active, critical, participatory, and responsible in democratic life.Keywords: Democratic Education, Political Awareness, Young Generation, Modern Era, Digital Literacy. Abstrak: Pendidikan demokrasi memiliki peran strategis dalam membentuk kesadaran politik generasi muda di tengah perkembangan teknologi dan transformasi ruang publik digital yang semakin kompleks. Penelitian ini bertujuan untuk menganalisis pengaruh pendidikan demokrasi terhadap kesadaran politik generasi muda di era modern. Penelitian menggunakan pendekatan kualitatif dengan metode studi literatur yang bersumber dari berbagai artikel jurnal, buku, dan dokumen ilmiah yang relevan. Analisis dilakukan melalui identifikasi, seleksi, dan sintesis berbagai temuan penelitian terkait pendidikan demokrasi, kesadaran politik, dan literasi digital. Hasil penelitian menunjukkan bahwa pendidikan demokrasi berkontribusi dalam meningkatkan pemahaman generasi muda mengenai hak dan kewajiban warga negara, memperkuat partisipasi politik, serta mengembangkan kemampuan berpikir kritis terhadap berbagai isu sosial, politik, dan kebijakan publik. Selain itu, media digital berfungsi sebagai sarana yang memperluas akses informasi politik dan ruang partisipasi warga negara. Namun, rendahnya literasi digital berpotensi meningkatkan risiko misinformasi dan disinformasi. Oleh karena itu, integrasi pendidikan demokrasi dan literasi digital diperlukan untuk membentuk generasi muda yang aktif, kritis, partisipatif, dan bertanggung jawab dalam kehidupan demokratis.Kata Kunci: Pendidikan Demokrasi, Kesadaran Politik, Generasi Muda, Era Modern, Literasi Digital